PENINGKATAN KAPASITAS MASYARAKAT DALAM BUDIDAYA UDANG VANAME (Litopenaeus vannamei) DAN KEPITING BAKAU (Scylla spp.) DI DESA PANYIWI, KECAMATAN CENRANA, KABUPATEN BONE - Anton Anton; Ani Leilani; Budiyati Budiyati; Muhammad Syahrir; Supryady Supryady; Yip Regan; Ihwan Ihwan; Yunarty Yunarty; Ardana Kurniaji; Siti Aisyah Saridu; Eriyanti Wahid; Diana Putri Renitasari; Muhammad Rasnijal; Zainal Usman (Universitas Mataram, 2022)
Vannamei shrimp and mangrove crabs are export commodities with high economic value. One of the areas that is central to the development of vaname shrimp and mangrove crab cultivation is in Bone Regency, South Sulawesi. The obstacle for vaname shrimp and mangrove crab cultivators is the lack of technical knowledge of environmentally friendly aquaculture. The lack of technology adaptation of cultivators is the reason for the importance of community service activities. This community service activity aims to increase public knowledge about the cultivation of vaname shrimp and mud crab. It is hoped that this activity can improve the welfare of the cultivating community, especially the cultivation of vaname shrimp and mangrove crabs. The methods used include socialization and training, monitoring of production activities and evaluation of activities. Socialization and training on technology and techniques for vaname shrimp cultivation and mud crab fattening. Monitoring is carried out starting from the pre-production, production to post-production stages. Evaluation is carried out to see the results of service activities. The results of the activity include the implementation of the activity stages, namely the formation of a group of vaname shrimp and mud crab cultivators, the implementation of training and outreach to farmers. The location for the cultivation of vaname shrimp and mud crab has been determined in accordance with the requirements for cultivation activities. Implementation of the process of assisting production activities to harvesting and marketing, followed by evaluation. The cultivator group has harvested 400 kg of vaname shrimp with a size of 130 and a mangrove crab of 75 kg with a maintenance period of 100 days. This activity has become the basis for cooperation and the beginning of the formation of synergy between academics, government and the community in Panyiwi Village, Cenrana District, Bone Regency. Community service activities carried out have increased people's income from the results of growing vaname shrimp in traditional ponds and fattening mangrove crabs.